2012
DOI: 10.1073/pnas.1212693109
|View full text |Cite
|
Sign up to set email alerts
|

π-Frontier molecular orbitals in S  = 2 ferryl species and elucidation of their contributions to reactivity

Abstract: S ¼ 2 FeIV ═O species are key intermediates in the catalysis of most nonheme iron enzymes. This article presents detailed spectroscopic and high-level computational studies on a structurallydefined S ¼ 2 Fe IV ═O species that define its frontier molecular orbitals, which allow its high reactivity. Importantly, there are both π-and σ-channels for reaction, and both are highly reactive because they develop dominant oxyl character at the transition state. These π-and σ-channels have different orientation dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
158
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(165 citation statements)
references
References 38 publications
7
158
0
Order By: Relevance
“…5). Similar stretch-induced oxyl formation has also been observed in calculations of Fe IV = O systems and stems from the propensity of a free O 2− ion to lower its energy by ejecting an electron (33,34).…”
Section: Resultsmentioning
confidence: 64%
“…5). Similar stretch-induced oxyl formation has also been observed in calculations of Fe IV = O systems and stems from the propensity of a free O 2− ion to lower its energy by ejecting an electron (33,34).…”
Section: Resultsmentioning
confidence: 64%
“…The d π* defines a π channel similar to the S = 1 Fe IV =O species, while d σ * arises from the strong σ antibonding interaction of the oxo p z with the Fe d z2 orbital and defines the σ channel for HAA that requires collinear orientation of the substrate C—H bond relative to Fe IV =O bond. 22 This additional σ channel in S = 2 complexes was elucidated on the basis of spin unrestricted MO theory as given in Figure 1. In going from an S = 1 to an S = 2 Fe IV =O system, the excitation of a β e − from the non-bonding d xy orbital into the α- d x2-y2 orbital leads to a considerable electron-electron exchange stabilization (referred in the literature to as spin polarization 20 or exchange enhancement 23 ) that shifts the α-MO manifold down in energy; thus the unoccupied α- d σ * becomes energetically comparable to the d π * FMOs and accessible for reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…[81,140] This HAA reactive channel flexibility hinted the importance of the S = 2 state for enzymatic selectivity. [144] Recently, the low temperature MCD spectroscopy in combination with CASPT2 and DFT calculations were used to define electronic structure of the NRVS-determined S=2 Fe IV =O active site in the halogenase SyrB2 and its contributions to H-atom abstraction that was shown to proceed via the (SFe=5/2) channel and to favor halogenation over hydroxylation enzymatic selectivity.…”
Section: Sfe=3/2)mentioning
confidence: 99%
“…[6,136,137,138,139,140] It was demonstrated that three different mechanisms exist for HAA, depending on the spin state of the complex (S = 1 vs. S = 2). [81,141,142] The triplet state, as the ground spin state of many synthetic NHFe IV =O compounds, effectively operates only through a " channel" with the C─H bond ideally oriented perpendicular to the Fe─oxo axis that allows the overlap of the substrate C─H orbital with one of the Fe=O d* FMOs. [141] In contrast, the quintet state which is the ground spin state in enzymatic NHFe IV =O structures, [143] has three HAA channels available: one " channel" that requires the C─H bond oriented in line with the FeO moiety (d* FMO overlapping with C─H) and two " channels"…”
Section: Mononuclear Ferryl Active Site: C─h + O=fe IV → C • + Ho─fe Iiimentioning
confidence: 99%